Analisis Dampak Beban Kerja Terhadap Kinerja Bidan Puskesmas XYZ - Novita Maharani; Dian Lestari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
An organization can achieve success if it is supported by good employee performance. The phenomenon behind this study is a decline in midwifery performance in the last three years. The purpose of this study is to determine the impact of workload on the performance of midwives at the XYZ Health Center. The number of informants in this study is 6 people who are concurrently in medical and administrative services (double job). The research method used in this study uses qualitative methods with data collection methods used, namely observation, interviews and documentation. The validity test of the data uses a triangulation process. The results of this study show that based on the informants' responses, the workload on midwives is in the high or inappropriate category, while performance is in the low category. This shows that workload has an impact on a person's performance.